Pengaruh Implementasi Sistem Total Quality Management dan Motivasi Kerja terhadap Kinerja Karyawan Pada Kantor Pusat Perusahaan Umum (Perum) BULOG - Renaldo Valentino Simanjuntak; Elmira Siska (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Public Company (Perum) BULOG is a business entity engaged in food logistics and has a strategic role in national food security. However, the company faces obstacles in the implementation of the Total Quality Management (TQM) system which is not fully in accordance with the applicable Standard Operating Procedures (SOP), as well as low work motivation for some employees. This study aims to analyze the influence of TQM implementation and work motivation on employee performance at the Perum BULOG head office. The research method used was a quantitative approach with data collection techniques through interviews and questionnaire distribution to 97 respondents selected using purposive sampling techniques. The research will be carried out in May 2025. The results of the analysis showed that partially, the implementation of TQM did not have a significant effect on employee performance (tcount = 1,533 < ttable = 1,985; sig. = 0.129 > 0.05). On the other hand, work motivation has a significant influence on employee performance (tcount = 5,411 > ttable = 1,985; sig. = 0.00 < 0.05). Simultaneously, TQM and work motivation had a significant effect on employee performance (Fcal = 16,602 > Ftable = 3,093; sig. = 0.00 < 0.05). These findings indicate that increasing work motivation is a key factor in encouraging employee performance, while the implementation of TQM needs to be adjusted to SOPs to be more effective in supporting organizational productivity.